Arthritogenic Alphaviruses: A Worldwide Emerging Threat? - Laura I. Levi; Marco Vignuzzi (Microorganisms, 2019)
Arthritogenic alphaviruses are responsible for a dengue-like syndrome associated with severe debilitating polyarthralgia that can persist for months or years and impact life quality. Chikungunya virus is the most well-known member of this family since it was responsible for two worldwide epidemics with millions of cases in the last 15 years. However, other arthritogenic alphaviruses that are as of yet restrained to specific territories are the cause of neglected tropical diseases: O’nyong’nyong virus in Sub-Saharan Africa, Mayaro virus in Latin America, and Ross River virus in Australia and the Pacific island countries and territories. This review evaluates their emerging potential in light of the current knowledge for each of them and in comparison to chikungunya virus.